Features of the microbiome of the gastrointestinal tract in patients with COVID-19 - E. N. Lazareva; V. V. Maleev; Zh. B. Ponezheva; N. S. Shvachkina; N. A. Tsvetkova (Лечащий Врач, 2025)
Background. COVID-19 is characterised by multimorbidity with involvement of not only respiratory organs, but also cardiovascular, urinary and nervous systems and gastrointestinal tract. Clinical symptoms of the disease are united in the gastrointestinal syndrome, registered in 30-79% of cases. The onset of the disease may be accompanied by diarrhoea in 50% of patients and may be combined with or preceded by nasopharyngeal catarrhal symptoms.Objective. To evaluate the features of the intestinal microbiota in patients with COVID-19, including those affected by the gastrointestinal tract.Materials and methods. In 85 patients diagnosed with a new coronavirus infection, the quantitative composition of the intestinal microbiota was assessed by the number of copies of microorganisms detected by PCR using the ENTEROFLOR test system.Results. A study of the structural composition of the intestinal microbiome has shown that patients with diarrhea have a statistically significant excess of copies of B. longum subsp. infantis, Bif. longum subsp. longum and B. breve against the background of a decrease in Bifidobacterium spp., B. adolescentis, B. bifidum and B. senulatum. Of the representatives of gram-negative commensals, Butyricimonas spp. was active. Among the opportunistic and pathogenic flora, an increase in the number of copies of Enterobateriaceae was noted, mainly in patients with diarrhea. They also more often identified S. aureus strains with mecA and C. dificile with resistance genes cdtA and сdtB. A direct correlation was established between C. dificile and Butyricimonas spp., as well as an inverse correlation between B. catenulatum and C. dificile cdtA and сdtB, and between Bifidobacterium spp. and S. aureus mecA.Conclusion. There is a decrease in gram-positive microorganisms among the commensals in favor of gram-negative microorganisms. Reduction of B. adolescentis and complete absence of B. bifidum and B. catenulatum in COVID-19 patients with diarrhea indicate the formation of inflammatory processes in the intestine. The transition to aerobic metabolism allows Enterobateriaceae to compete with beneficial obligate anaerobes, with the growth of strains containing resistance genes.